The Contribution of Practical Readiness and Practice Intensity to Women's Fashion Learning Outcomes in Grade XI Students at State Vocational High School 4 Yogyakarta - Anto, Bagus Irwan; Saryanto, Saryanto (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to analyze the contribution of practical readiness and practice intensity to women's fashion learning outcomes in grade XI students at State Vocational High School 4 YogyakartaMethodologyA quantitative approach with a survey method was employed. The sample comprised 32 grade XI Fashion 4 students selected purposively. Data were collected using Guttman-scale questionnaires for practical readiness and practice intensity, and documentation of practical scores. Simple regression analysis was performed using statistical softwareMain Findings: Practical readiness and practice intensity were both in the high category. They contributed 30.0% and 25.2% respectively to learning outcomes, with a combined contribution of 55.2%. Students' average learning outcome score was 87.45, far exceeding the minimum completion criteria.Novelty/Originality of this study: This research integrates two internal student factors practical readiness and practice intensity into a single contributory model for fashion learning outcomes in a naturalistic vocational school setting. It provides new insights into determinants of practical competency, offering best practices for fashion education